About the Potential of E-democracy in Cooperative Organisations - José Monserrat Neto (tripleC: Communication, Capitalism & Critique)
This paper develops a reflection on the potential of e-democracy to strengthen society's democratization exploring historically and technically the possibilities of cooperative organisations. From Singer's historical view about the rise of capitalism it is conjectured that Internet and e-democracy could be the technological innovations capable to trigger off the creation of a virtual network of cooperative organisations and thereby the development of a new economic system, based more on humanitarian values than the present ones.